Iron Recovery from Residue of Lateritic Nickel Leaching Industry - Permatasari Nur V. (EDP Sciences, 2021)
HPAL (High-Pressure Acid Leaching) is one of the important technologies for extracting nickel and cobalt from nickel laterite ore. In the next few years, some plants using this technology will be operated in Indonesia. The production will be estimated to be 543,000 tons per year by 2025. On the other hand, HPAL will produce more than 26 million tonnes of residue, and it requires good management. The residue utilization for certain industrial raw materials is one of the solutions. To determine the potential utilization residue, the characteristic of the residue must be elaborated through some methods. The characterization is carried out based on mineralogical and chemical properties. The feed used in the HPAL process dominates with magnetite and goethite with 41,15 % Fe and 1,35 % Ni content. The residue of HPAL contains Fe and significant Sulphur content, silica, aluminium and calcium. The quantity of Sulphur must be decreased by the desulfurization method then followed by the reduction process. The analysis shows that HPAL residue is still required additional processing for reducing the Sulphur content. The residue utilization trial still needs to be done to determine the quality of the iron-making products produced produced.